The role of the public health nurses in the 1932’s Drought (Research, Society and Development, 2022)
This article reports the analysis of the written content of the “Relatório da Comissão Médica de Assistência e Profilaxia aos Flagelados no Nordeste'' about the role of nurses who belonged to the board of employees of the National Department of Public Health (DNSP) during the drought of 1932-33. The historic document is a report published in 1936 by the DNSP and references the work of a federal commission composed by fifteen nurses and four doctors, who left the Federal District to organize the assistential fields of the drought’s flagellated, located on the “sertões'' of Ceará, Rio Grande do Norte e Paraíba. The analysis allowed us to know the work of these comissionated nurses at the coordination and organisation of care fields under the sanitary districtal model’s logic, in scenes of disadvantageous conditions compared to the ones found at large capitals of the country. The analysis of the implantation of prophylaxis measures against diseases and the accomplishment of health vigilance and education to the population located at the assistance fields helped on the nursing path as a career at the country’s rural recesses as filled important gaps in the history of expansion and consolidation of health services at the northwest’s semiarid.